Palladium-Catalyzed Reaction of Propargylic Carbonates with Benzyne - Ni, Shengjun; Shu, Wei; Ma, Shengming (Synlett, 2013)
Under the catalysis of palladium acetate, 1,2-allenylpalladium formed from propargylic carbonates may react with two molecules of benzyne to afford phenanthrene derivatives by cyclization and β-H elimination.
Keywords: propargylic carbonates; allenylpalladium; phenanthrene derivatives; cyclization; β-H elimination